2004
DOI: 10.1046/j.1351-5101.2003.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Spasms in children with definite and probable mitochondrial disease*

Abstract: The diagnosis of mitochondrial encephalomyopathies is complex and a system for classification of the diagnosis as definite, probable, and possible has been proposed. The objective of this study was to explore the spectrum of epileptic disorders associated with probable and definite mitochondrial disease in children using this classification system. The patient population with mitochondrial disease and epilepsy was selected from a tertiary care children's hospital. Interictal electroencephalograms and video-EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(79 reference statements)
0
6
0
1
Order By: Relevance
“…There have been several sporadic reports discussing MRC enzyme defects or named mitochondrial dysfunction syndromes that are associated with epileptic conditions such as West syndrome, but none have collectively reported on the spectrum of epilepsy caused by MRC defects (Shoffner et al, 1990; Jaksch et al, 1998; Sadleir et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several sporadic reports discussing MRC enzyme defects or named mitochondrial dysfunction syndromes that are associated with epileptic conditions such as West syndrome, but none have collectively reported on the spectrum of epilepsy caused by MRC defects (Shoffner et al, 1990; Jaksch et al, 1998; Sadleir et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the difficulty in diagnosing some mitochondrial diseases. Normal blood and CSF lactate are not uncommon in children with a mitochondrial disease 11 . Sadleir et al demonstrated that forty percent of children with confirmed or suspected mitochondrial disease had infantile spasms, while conversely eight percent of all children with spasms were shown to have a mitochondrial disease 11 .…”
Section: Discussionmentioning
confidence: 98%
“…Atypical absence, primary generalized and atonic events can also occur, although isolated generalized epilepsy is rare in mitochondrial disease. Infantile spasms (West syndrome) do not occur frequently and are seen more commonly in pyruvate dehydrogenase deficiency [Sadleir et al, 2004]. It is possible that mitochondrial diseases remain underdiagnosed in children with West syndrome [Blanco-Barca et al, 2004].…”
Section: Epilepsymentioning
confidence: 99%